HORMONAL AND PSYCHOLOGICAL DETERMINANTS OF POSTPARTUM BODY IMAGE AND THE DESIRE FOR AESTHETIC ENHANCEMENT - Agata Lurka; Agata Panfil; Katarzyna Kleszczewska; Agnieszka Pruska; Natalia Senatorska; Julia Rarok; Daria Godlewska; Hanna Pietruszewska; Monika Banaszek; Julia Błocka (International Journal of Innovative Technologies in Social Science, 2025)
Background: The postpartum period brings intense biological, psychological, and social change . The female body rapidly recalibrates hormones, recovers physically, and reorganizes identity. All this happens under cultural scrutiny and unrealistic expectations. Understanding these interactions is essential for supporting maternal well-being and interpreting the growing demand for postpartum aesthetic enhancement .Objective: To review the hormonal and psychological determinants of postpartum body image and explore their connection to the desire for aesthetic enhancement.Methodology: A narrative review was conducted using PubMed/MEDLINE, Scopus, and PsycINFO. Keywords were postpartum, body image, hormones, estrogen, progesterone, oxytocin, prolactin, cortisol, thyroid, depression, anxiety, and cosmetic surgery. Studies, meta-analyses, and reviews on women within 24 months postpartum were included.Results: Endocrine fluctuations, especially in estrogen, progesterone, oxytocin, prolactin, cortisol, and thyroid hormones, shape mood, energy, and body perception. Psychological factors include depression, anxiety, self-esteem, self-compassion, partner support, and sociocultural norms. These mediate the connection between biological recovery and body satisfaction .Conclusions: Postpartum body image is shaped by dynamic hormonal, psychological, and cultural factors. Patient-centered care should be integrative. It should include hormonal monitoring, psychosocial support, and realistic counseling on aesthetic procedures. Such care promotes maternal well-being and autonomy.